Investigation of the irisin, preptin and adropin levels in the blood serum of Alburnus tarichi - Caf, F.; Algul, S.; Koyun, M. (Cellular and Molecular Biology, 2017)
Irisin, preptin and adropin are three newly discovered peptides that play critical roles in regulating energy homeostasis in various vertebrates.The purposes of this study were to measure the serum concentrations of preptin, adropin and irisin in the Alburnus tarichi and to investigate the relationship of these peptides to the weight, gender and length of this the fish, which will provide useful information for future biotechnology purposes aimed at improvements in aquaculture production. This study used 12 adult A. tarichi (6 female and 6 male) obtained from Van Lake (Van, Turkey). The serum irisin, preptin and adropin levels were measured using a commercially available enzyme-linked immunosorbent assay (ELISA) kit to determine correlations between the levels of these three hormones and fish body weight and length. No statistically significant correlations were detected between the serum irisin, adropin and preptin levels and A. tarichi body weight (p = 0.921, r = -0.031; p = 0.08, r = 0.519; p = 0.461, r = -0.235, respectively) or length (p = 0.901, r = -0.040; p = 0.105, r = 0.490; p = 0.236, r = -0.369, respectively).Thus, serum levels of these hormones are independent of fish gender, body weight and length.